Hubungan Indeks Massa Tubuh Terhadap Usia Menarche Pada Siswi Kelas 5 dan 6 SD Negeri 09 Kayu Putih Dan Siswi Kelas 7 SMP Negeri 77 Jakarta Dan Tinjauannya Menurut Pandangan Islam - Annisa Nurvita Indah; Amelia Kresna; Siti Maulidya Sari; Arsyad Arsyad (Jurnal Ners, 2026)
Menarche is an important marker of puberty in adolescent girls and is influenced by various factors, one of which is nutritional status measured by Body Mass Index (BMI). This study aims to analyze the relationship between BMI and the age of Menarche among fifth- and sixth-grade students at SDN 09 Kayu Putih and seventh-grade students at SMPN 77 Jakarta. The research employed a quantitative method with a cross-sectional design. Respondents were selected using purposive sampling, involving 97 students who met the inclusion criteria. Data were collected through measurements of body weight and height as well as questionnaire administration. Data analysis was conducted using the Chi-Square test. The results showed a significant association between BMI and age of Menarche (p-value 0.000). A total of 79.3% of respondents with overweight BMI status and 84.6% with obesity experienced early Menarche (age <12 years). Respondents with normal BMI had a more varied distribution of Menarcheal age, with the majority falling into the normal category (12–14 years). From an Islamic perspective, maintaining balanced nutrition through the consumption of halal and thayyib foods is emphasized as essential for supporting bodily and reproductive health. The conclusion of this study is that there is a significant relationship between BMI and the age of Menarche, in which excessive nutritional status tends to accelerate the onset of Menarche.